KNOWLEDGE AND PERCEPTIONS ON THE READING OF FOOD LABELS: A CASE STUDY IN URUGUAY - Laura Raggio; Valeria Berrondo (Universidade do Estado do Rio de Janeiro, 2018)
Food labeling is one of the tools that consumers use to make choices when buying food products. This study aimed at evaluating some knowledge regarding labeling of packaged foods among one convenience sample comprising consumers in Uruguay, over 18 years of age. Our findings are similar to those found in other Latin American studies aimed at understanding and helping the consumer make a conscious and informed purchase of packaged products. Among respondents, 88% declared they read food labels. Based on the most read information provided in the labels, the expiration date was the most mentioned. Specifically in relation to nutritional information, the fat content was considered the most relevant fact, whereas the protein content was the least relevant one. The technical concept of portion seems to be understood by more than half of the respondents. But the same was not observed in relation to the concept of light. This study reflects the lack of knowledge regarding fundamental nutritional aspects in people's lives. Working towards clear food labels and a constant high-standard education on this issue is crucial to cause an impact on the food choices and the consumption of healthy food products, besides raising public awareness about how appropriate food choices can contribute to health maintenance and prevention of diseases.  DOI: 10.12957/demetra.2018.32827